Determiners : universals and variation - Ghomeshi, Jila; Paul, Ileana; Wiltschko, Martina (Linguistik aktuell, 2009)
This volume brings together recent work on the formal and interpretational properties of determiners across a variety of typologically and geographically unrelated languages. It seeks to answer the core question of modern linguistic theory: Which properties of languages are universal and which are variable? In recent theorizing, much of language variation is argued to stem from differences in the properties of features associated with functional heads. As such, this volume can be viewed as a case study of one such category: the determiner (D). The contributions all investigate the status of D.